Improving the safety of fresh fruit and vegetables - Jongen, W. M. F. (Woodhead Publishing in food science and technology., 2005)
Fresh fruit and vegetables have been identified as a significant source of pathogens and chemical contaminants. As a result, there has been a wealth of research on identifying and controlling hazards at all stages in the supply chain. Improving the safety of fresh fruit and vegetables reviews this research and its implications for food processors. Part one reviews the major hazards affecting fruit and vegetables such as pathogens and pesticide residues. Building on this foundation, Part two discusses ways of controlling these hazards through such techniques as HACCP and risk assessment. The final part of the book analyses the range of decontamination and preservation techniques available, from alternatives to hypochlorite washing systems and ozone decontamination to good practice in storage and transport. With its distinguished editor and international team of contributors, Improving the safety of fresh fruit and vegetables is a standard reference for all those involved in fruit and vegetable production and processing. Reviews recent research on controlling hazards at all stages of the supply chainDiscusses the implications of this research on food processorsDiscusses the implications of this research on food processors.